Interpolation Property on Visser’s Formal Propositional Logic - Alizadeh, Majid; Memarzadeh, Masoud (Bulletin of the Section of Logic, 2022)
In this paper by using a model-theoretic approach, we prove Craig interpolation property for Formal Propositional Logic, FPL, Basic propositional logic, BPL and the uniform left-interpolation property for FPL. We also show that there are countably infinite extensions of FPL with the uniform interpolation property.